Biochemical changes in the larval stages of an edible estuarine crab Thalamita crenata (Latreille) fed with different diets - Kannupandi, T; Murugadasu, P; Soundarapandian, P; Shanmugam, A (Indian Journal of Fisheries, 2011)
When the larvae were fed with Coscinodiscus sp. and Ariemia naupHi diets, the development was complete and the protein content increased from first zoeal stage to fifth zoeal stage and decreased in megalopa stage. Lipid content showed a steady increase in all the stages; but the carbohydrates content showed an increase upto third zoeal stage then a decrease in the fourth and fifth zoeal stages and again an increase in the megalopa stage. In general, when the larvae were fed with Thalassiothrix longissima, Nitzschia sp. and Skeletonema sp., more carbohydrate accumulated. But when the larvae were fed with Artemia nauplii and Coscinodiscus sp., protein and lipid increased during the larval development.